Biosynthesis of aliphatic plastic monomers with amino residues in Yarrowia lipolytica - Park, Gyuyeon; Kim, Ye Chan; Jang, Minjeong; Park, Hyuna; Lee, Hong-Weon; Jeon, Wooyoung; Kim, Byung-Gee; Choi, Kwon-Young; Ahn, Jungoh (Frontiers in Bioengineering and Biotechnology, 2023)
used as building blocks in polymer industries. Medium- to long-chain (C8 to C18) fatty acid monomers with amino residues are almost exclusively produced via chemical processes that generate hazardous waste and induce severe environmental problems, such as global warming and pollution. Here, we present the construction platform strains of Yarrowia lipolytica, a cheese-ripening yeast, for direct biotransformation of hydrocarbons into medium- to long-chain ,-diamines and -amino fatty acids using metabolic engineering of endogenous fatty acid ω- and β-oxidation pathways and introducing heterologous ω-transaminase in Y. lipolytica. We deleted six genes encoding the acyl-CoA oxidase (ACO1–6) and four fatty aldehyde dehydrogenase genes (FALDH1–4), which catalyze fatty acid oxidation and downstream oxidation of fatty aldehydes in Y. lipolytica, respectively. The ω-transaminase from Chromobacterium violaceum DSM30191 was introduced into the genome of the ΔPOX ΔFALDH strain under the control of Y. lipolytica-derived EXP1 promoters. The ΔPOX ΔFALDH strains with ω-CvTA successfully accumulated the corresponding C12 ,-diamines into a shaking culture medium with dodecane or dodecanol. In addition, these strains accumulated C12 -amino fatty acids from dodecanoic acid. With the commercially available -diacid bioprocess, this yeast biosynthesis producing medium- and long-chain ,-diamines and -amino fatty acids could complete the yeast platform technology generating all medium- and long-chain aliphatic polyamide monomers, ,-biofunctionalized with one or both carboxylic acid or amino residues.